Analisis Hubungan Kualitas Hidup Terhadap Penggunaan Kombinasi Obat Antipsikotik Pada Pasien Skizofrenia - Godeliva Adriani Hendra (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2020)
Therapy of schizophrenic patients often starts with treatment. In addition to psychosocial support therapy, treatment for schizophrenia can use a combination of antipsychotic drugs. The use of a combination of antipsychotic drugs causes various side effects and drug interactions that affect the quality of life of patients. The purpose of this study was to determine the correlation of quality of life to a combination of antipsychotic drugs at the Sumberpucung Health Center. The study design used a cross-sectional retrospectively with descriptive statistical tests and chi-square. There were 37 respondents who were divided into 16 respondents using a combination of A (chlorpromazine, haloperidol) and 21 respondents using a combination of B (Haloperidol, Trihexyphenidyl), (Chlorpromazine, Trihexyphenidyl, Trifluoperazine), (Chlorpromazine, Trihexyphenidyl, Haloperidol), (haloperidol, Clozapine), (Chlorpromazine, Risperidone), (Trihexyphenidyl, Risperidone), (Trihexyphenidyl, Trifluoperazine, Clozapine), (Trihexyphenidyl, Risperidone, Clozapine), (Chlorpromazine, Trihexyphenidyl, Risperidone), (Haloperidol, Trihexyphenidyl, Trifluoperazine), (Haloperidol, Trifluoperazine). Interview with respondents regarding quality of life using the WHOQOL-BREF questionnaire which was divided into 4 domains. Each domain was analyzed based on the good and poor quality of life, history of antipsychotic drug use reviewed from the previous 3 months. The questionnaire has been validated and reliable. The results showed there was a correlation between the quality of life with the use of a combination of antipsychotic drugs (p <0.05). Based on the results of the study found the combination of B provides a better quality of life because the combination of B has lighter side effects for treating symptoms in schizophrenic patients.